A model for identifying intensity zones above critical velocity - Bergstrom, H. C.; Housh, T. J.; Cochrane-Snyman, K. C.; Jenkins, N. D. M.; Byrd, M. T.; Switalla, J. R.; Schmidt, R. J.; Johnson, G. O. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to describe the VO2 responses relative to VO2peak at 4 different intensities within the severe domain and, based on the VO2 responses, identify intensity zones above critical velocity (CV). Twelve runners (mean ± SD age = 23.2 ± 3.0 years) performed an incremental treadmill test (ITT) to exhaustion to determine the VO2peak and velocity associated with VO2peak (vVO2peak). Critical velocity was determined from 4 exhaustive, constant velocity, randomly ordered treadmill runs (V 1, V 2, V 3, and V 4; V 1 = highest, V 4 = lowest). The VO2 responses were recorded during each of the constant velocity runs. Mean differences among VO2peak values from the ITT and the highest value recorded during the constant velocity runs were examined. The VO2 values at exhaustion for V 1 (3.32 ± 0.10 L/min, p = 0.15) and V 2 (3.27 ± 0.91 L/min, p = 0.13) were not significantly different from VO2peak (3.39 ± 0.96 L/min) from the ITT. The VO2 values at exhaustion for V 3 (3.18 ± 0.88 L/min; p = 0.007) and V 4 (3.09 ± 0.86 L/min; p = 0.003), however, were significantly less than the VO2peak from the ITT. There were intensity-dependent VO2 responses above CV. Based on these findings, we have hypothesized 3 intensity zones (first severe intensity zone [SIZ1], second severe intensity zone [SIZ2], and extreme intensity zone [EIZ]) within the severe and extreme domains, which are characterized by specific VO2 responses and may be used to design programs that maximize aerobic performance adaptations.